Fluorinated Electrolyte Compound as a Bi-Functional Interphase Additive for Both, Anodes and Cathodes in Lithium-Ion Batteries. Issue 14 (15th November 2018) - Janssen, Pia; Kasnatscheew, Johannes; Streipert, Benjamin; Wendt, Christian; Murmann, Patrick; Ponomarenko, Maksym; Stubbmann-Kazakova, Olesya; Röschenthaler, Gerd-Volker; Winter, Martin; Cekic-Laskovic, Isidora
Abstract : Lithium-bis(hexafluorobutan-2, 3-diol)-borate (R1S), synthesized as a novel electrolyte component in lithium-ion battery (LIB) cells, was evaluated and introduced as a bifunctional interphase additive for both, anodes and cathodes with the purpose of improving the cell performance during high voltage operation. For the graphite based anode it was demonstrated, that the additive could diminish the amount of parasitic capacity required for the formation of an effective solid electrolyte interphase (SEI), which could be concluded from improved Coulombic efficiency data. In parallel, improved capacity retention on the cathode attributed to an altered cathode electrolyte interphase (CEI) by the same additive was observed. Contrary to the CEI formed by the benchmark electrolyte formulation, the interphase of the additive containing electrolyte formulation is significantly influenced in an electrochemical manner (oxidation reactions), as derived from potentiodynamic measurements. As a result, the additive-tuned CEI was found smoother and less resistive compared to the additive-free counterpart, which was demonstrated by electrochemical impedance spectroscopy (EIS), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) of the harvested LiNi1/3 Co1/3 Mn1/3 O2 (NMC111) electrodes after charge/discharge cycling. The simultaneous improvement of the interphases on cathode and anode by the additive could finally enhance the overall performance of a NMC111/graphite cell.